Effects of Myroxylon peruiferum L. f. organic extracts in planktonic growth and Ralstonia solanacearum biofilm formation - Malafaia, Carolina Barbosa; Houllou, Laureen Michelle; Barbosa, Mariana Oliveira; Souza, Elineide Barbosa de; Macedo, Alexandre José; Silva, Alexandre Gomes da; Correia, Maria Tereza dos Santos; Silva, Márcia Vanusa da (Journal of Environmental Analysis and Progress, 2019)
Ralstonia solanacearum, a causal agent of bacterial wilt, a disease with significant negative impacts on world agriculture, presents considerable difficulties in handling due to its resistance to the common forms of control. Based on this context, the objective of this work was to investigate alternative substances for biofilm control and planktonic growth of this phytopathogen. Four organic extracts in the eluotropic series (cyclohexane, chloroform, athyl acetate, and methanol) of Myroxylon peruiferum collected in the Caatinga were evaluated for antibiofilm and antibacterial activity using the crystal violet method and antibacterial activity in microplates, considering positive values greater than 50% inhibition. The organic extracts were evaluated qualitatively by thin layer chromatography. Results obtained showed that antibiofilm activity was detected in the cyclohexanic extract, whereas ethyl acetate extract showed antibiotic activity, both in the minimum inhibitory concentration of 3 mg/mL. The evaluation presented in this study provides a database for the development of new natural phytopathogen control agents.